إشكالية دمج الاقتصاد الخفي ضمن الاقتصاد الرسمي في الجزائر - عمامرة, ياسمينة; ممو, سعيدة; عوادي, مصطفى (جامعة الوادي - University of Eloued, 2021)
يهدف البحث إلى محاولة تحليل إمكانية دمج الاقتصاد الخفي ضمن الاقتصاد الرسمي في الجزائر، وذلك من خلال محاولة تقدير قيمة الاقتصاد الخفي دوليا ووطنيا، خاصة في ظل الانفتاح الاقتصادي والتحرر المالي والاتجاه لتبني إصلاحات شاملة بغية الخروج من النكسة التي سببها التغير المستمر لأسعار البترول في الأسواق العالمية. وقد توصل البحث إلى أن الجزائر قد اعتمدت على تطبيق استراتيجيات لدمج الاقتصاد الخفي في الاقتصاد الجزائري من خلال آليات تفكيك الاقتصاد الخفي ودمجه في الاقتصاد الرسمي. The aim of this research is to try to analyze the possibility of integrating the hidden economy into the official economy in Algeria by trying to estimate the value of the hidden economy internationally and nationally, especially in the light of economic openness and financial liberalization and the trend towards adopting comprehensive reforms in order to overcome the setback caused by the continuous change in oil prices in international markets. The study concluded that Algeria has relied on the application of strategies to integrate the hidden economy into the Algerian economy through mechanisms to dismantle the hidden economy and integrate it into the formal economy
The problem of integrating the hidden economy into the formal economy in Algeria
مقال
Keywords: اقتصاد خفي ; اقتصاد رسمي ; استراتيجيات الدمج ; اليات الدمج